Fibroblastic connective tissue nevus: Clinicopathological and immunohistochemical study of 14 cases - Pennacchia, Ilaria; Kutzner, Heinz; Kazakov, Dmitry V; Mentzel, Thomas (Journal of cutaneous pathology, 2017)
BACKGROUND: We present herein a series of 14 lesions showing overlapping features with the newly defined benign cutaneous mesenchymal neoplasm labeled as fibroblastic connective tissue nevus (FCTN). METHODS AND RESULTS: Total of 8 patients were male and 5 were female, ranging in age from 1 to 56 years. Lesions appeared as isolated nodules or plaques on the trunk (7 cases), the limbs (4 cases) and the neck (2 cases). Histologically, all cases were composed of bundles of bland spindle cells of fibroblastic/myofibroblastic lineage irregularly branching within the reticular dermis and along fibrous septa in the subcutis. Adnexal structures and dermal adipocytes were entrapped by the fascicles, the epidermis was often papillomatous and elastic fibers were decreased and fragmented. Expression of CD34 and ASMA was found in 8 and 7 cases, respectively. Follow-up was available for 7 patients (mean follow-up, 5 years; range, 1-10 years). None of the cases metastasized or recurred, even when incompletely excised. CONCLUSION: The differential diagnosis of FCTN is broad and includes hypertrophic scar, dermatofibroma, dermatomyofibroma, pilar leiomyoma, plaque-stage DFSP, CD34-positive plaque-like dermal fibroma, fibroblastic-predominant plexiform fibrohistiocytic tumor, lipofibromatosis, superficial desmoid fibromatosis and fibrous hamartoma of infancy, of which it represents probably the monophasic variant.
Keywords: keratinocyty; dermatomyofibroma; mužské pohlaví; fibroblastic-myofibroblastic tumors; Male; intradermální névus; Female; Humans; kojenec; škára; Dermis; myofibroblasty; Nevus, Intradermal; lidé; Myofibroblasts; Middle Aged; ženské pohlaví; lidé středního věku; Infant; Skin Neoplasms; Neoplasm Proteins; mladiství; nádorové proteiny; Child; dítě; Adolescent; skin; Child, Preschool; dospělí; Antigens, CD34; Adult; Keratinocytes; nádory kůže; předškolní dítě; antigeny CD34; fibrous hamartoma of infancy; fibroblastic connective tissue nevus